Perioperative Treatment in EGFR‐Mutant Early‐Stage Non‐Small Cell Lung Cancer: Current Evidence and Future Perspectives - Xiaobei Guo; Xiaoyan Liu; Chao Guo; Qian Miao; Xinghua Cheng; Xuan Hong; Hongru Li; Xiaoming Qiu; Yi Xiang; Di Zheng; Jian Zhou; Liyan Jiang; et al. (Thoracic Cancer)
ABSTRACT Adjuvant osimertinib administered over a 3‐year period in patients diagnosed with stage IB–IIIA non‐small cell lung cancer (NSCLC) and epidermal growth factor receptor (EGFR) mutations has not only shown improvement in event‐free survival but also demonstrated a prolonged overall survival (OS), leading to its approval as a standard treatment in this context. Meanwhile, no targeted studies have been conducted on the efficacy of adjuvant immune checkpoint inhibitors in these patients. Although studies such as IMPOWER‐010 and KEYNOTE‐091 have included a small number of patients with positive driver genes, no definitive conclusions regarding the OS benefit have been established. Neoadjuvant targeted therapy is not currently recommended because of insufficient evidence, characterized by a low depth of pathological response and no reported improvement in survival outcomes. The same is true for neoadjuvant immunotherapy in patients with EGFR mutations. Although numerous issues such as refining patient population selection, determining appropriate combination therapy regimens, establishing primary endpoints, assessing the influence of perioperative complications, and accurately evaluating the clinical application of circulating tumor DNA in various scenarios exist, several promising ongoing trials, including ADAURA2 and NEOADURA, are expected to provide valuable insights that will help address these questions. Here, we summarize the available evidence and clinical issues that need to be considered to optimize clinical decision‐making for patients with EGFR‐mutant NSCLC.